RESPON TANAMAN KALE (Brassica oleracea var. acephala) TERHADAP FREKUENSI DAN KONSENTRASI POC LIMBAH CAIR TAHU SECARA HIDROPONIK - Alpandari, Heny; Krestiani, Veronica; Abiyyu, Dhiaulhaq (Fakultas Pertanian, Universitas Janabadra, 2024)
Research regarding the use of liquid organic fertilizer from tofu waste has been carried out previously, both hydroponically and conventionally on several types of plants. Therefore, the aim of this research is to examine the response of Kale plants (Brassica oleracea var. acephala) to the frequency and concentration of giving liquid organic fertilizer from tofu waste hydroponically. This research used a Completely Randomized Design (CRD) which consisted of 2 factors and was repeated four times. The first factor is the frequency of administration 1x (7 dap), 2x (7 & 21 dap), 3x (7,21 and 30 dap). The second factor is concentrations of 25%, 50% and 75%. The parameters observed were plant height, number of leaves, root length, fresh weight and dry weight of the plant. The results obtained from this panel were that the frequency and concentration of liquid organic fertilizer of tofu liquid waste had an effect on all observation parameters, namely plant height, number of leaves, root length, fresh weight and dry weight of Kale plants. The treatment that gives better results is the frequency of administration 3 times with a concentration of 50%.